Education 2030 - Achievements of TVET in Asia and The Pacific along with The Fourth Industrial Revolution - Wickramasinghe, GLD; Wickramasinghe, Vathsala (Journal of Technical Education and Training, 2025)
The modernization of TVET has not occurred with a system-wide approach covering the entire spectrum of TVET institutes worldwide. The literature that incorporates the Sustainable Development Goal for Education (SDG4) and the fourth industrial revolution in TVET is very rare to be found from international and comparative standpoints since these areas are still emerging. Further, case-based or single country-based experiences do not provide sufficient information to make informed decisions. Therefore, more empirical studies are needed on the adoption of SDG4 in TVET institutes to gain a broad-based understanding of the prevailing context. Given these gaps in the scholarship, the present study investigated the status of the adoption of SDG4 in TVET institutes. Accordingly, the study collected data covering the areas of 1) the teaching and learning context, 2) steps taken to impart skills for employment, and 3) steps taken to enhance the capacities of staff in response to the changing world of work from fifteen Asian and Pacific countries. Four hundred and twenty-eight TVET staff responded to the survey. The findings showed significant differences by the regional classification of the country and by the type of TVET institute. The findings of the study are novel and provide ample evidence for the status of TVET in incorporating SDG4 in the fourth industrial revolution era. The findings also showed that the policymaking bodies must take active measures to increase responsiveness in fulfilling SDG4 and addressing challenges brought about by the fourth industrial revolution technologies.